PENGGUNAAN METODE BERMAIN PERAN (ROLE PLAYING) DALAM MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR PKN SISWA KELAS VI SD NEGERI 016 KUNDUR - Mustafa Mustafa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
Classroom action research was conducted to grade 6 students at SD Negeri 016 Kundur. The purpose of the study isto improve student learning outcomes with the subject of struggle values in the formulation of Pancasila. Efforts toimprove learning outcomes, researchers use role playing methods. After implemented the method of learningprocess has seen the spirit of students learn because the role playing method (role playing) students directly do thelearning. Improved learning outcomes began to change. Prasiklus is not complete as many as 10 people (41.67%),complete as many as 14 people (58.33%). In the first cycle, the result of study was increased by 7 people (29,83%)and complete 17 people (70,83%). In cycle II. All students have completed the learning process with a total of 24people (100%). So it can be concluded that the role playing method (role playing) can improve the learningoutcomes of Civics students class VI SD Negeri 016 Kundur.